Solid electrolyte material and battery using same

By using solid electrolytic materials including lithium, titanium, zirconium and fluorine, and synthesizing by mechanochemical grinding, the shortcomings of high lithium ion conductive materials in the prior art are solved, and the effects of high conductivity and high oxidation stability are achieved.

JP7660287B2Active Publication Date: 2025-04-11PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022508068
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-18
Filing Date
2020-12-22
Publication Date
2025-04-11
Estimated Expiration
2040-12-22

AI Technical Summary

Technical Problem

The prior art is difficult to provide a solid electrolytic material with high lithium ion conductivity.

Method used

Solid electrolytic materials including lithium (Li), titanium (Ti), zirconium (Zr) and fluorine (F) are used to synthesize them through mechanochemical grinding to ensure the high lithium ion conductivity of the material.

Benefits of technology

High lithium ion conductivity is achieved and sulfur-free, the formation of hydrosulfide is avoided, and the oxidation stability of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660287000002
    Figure 0007660287000002
  • Figure 0007660287000003
    Figure 0007660287000003
  • Figure 0007660287000004
    Figure 0007660287000004
Patent Text Reader

Abstract

This solid electrolyte material contains Li, Ti, Zr, and F.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a solid electrolyte material and a battery using the same. [Background technology]

[0002] Patent Document 1 discloses an all-solid-state battery using a sulfide solid electrolyte. Patent Document 2 discloses LiBF4 as a fluoride solid electrolyte material. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-129312 A [Patent Document 2] JP 2008-277170 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide a solid electrolyte material having high lithium ion conductivity. [Means for solving the problem]

[0005] The solid electrolyte material of the present disclosure includes Li, Ti, Zr, and F. Effect of the Invention

[0006] The present disclosure provides a solid electrolyte material having high lithium ion conductivity. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 shows a cross-sectional view of a battery 1000 according to a second embodiment. [Diagram 2] FIG. 2 shows a cross-sectional view of a battery 2000 according to a second embodiment. [Diagram 3]FIG. 3 shows a schematic diagram of a pressing die 300 used to evaluate the ionic conductivity of a solid electrolyte material. [Figure 4] FIG. 4 is a graph showing a Cole-Cole plot obtained by impedance measurement of the solid electrolyte material according to Example 1. [Diagram 5] FIG. 5 is a graph showing the initial discharge characteristics of the batteries according to Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.

[0009] (First embodiment) The solid electrolyte material according to the first embodiment contains Li, Ti, Zr, and F. The solid electrolyte material according to the first embodiment has high lithium ion conductivity. Here, the high lithium ion conductivity is, for example, 1×10 -8 That is, the solid electrolyte material according to the first embodiment has a dielectric constant of, for example, 1×10 -8 The ionic conductivity may be 1.0 S / cm or more.

[0010] The solid electrolyte material according to the first embodiment can be used to obtain a battery having excellent charge / discharge characteristics. An example of the battery is an all-solid-state battery. The all-solid-state battery may be a primary battery or a secondary battery.

[0011] The solid electrolyte material according to the first embodiment desirably does not contain sulfur. A solid electrolyte material that does not contain sulfur is excellent in safety because it does not generate hydrogen sulfide even when exposed to the atmosphere. The sulfide solid electrolyte disclosed in Patent Document 1 may generate hydrogen sulfide when exposed to the atmosphere.

[0012] The solid electrolyte material according to the first embodiment contains F, and therefore can have high oxidation resistance. This is because F has a high redox potential. On the other hand, F has a high electronegativity, and therefore the bond with Li is relatively strong. As a result, the lithium ion conductivity of a solid electrolyte material containing Li and F is usually low. For example, LiBF4 disclosed in Patent Document 2 has a lithium ion conductivity of 6.67×10 -9 LiBF4 has a low ionic conductivity of, for example, 1×10 -8 It can have a high ionic conductivity of S / cm or more.

[0013] In order to increase the ionic conductivity of the solid electrolyte material, the solid electrolyte material according to the first embodiment may contain anions other than F. Examples of such anions are Cl, Br, I, O, S, or Se.

[0014] The solid electrolyte material according to the first embodiment may be substantially composed of Li, Ti, Zr, and F. Here, "the solid electrolyte material according to the first embodiment is substantially composed of Li, Ti, Zr, and F" means that the molar ratio (i.e., molar fraction) of the total amount of substance of Li, Ti, Zr, and F to the total amount of substance of all elements constituting the solid electrolyte material according to the first embodiment is 90% or more. As an example, the molar ratio may be 95% or more. The solid electrolyte material according to the first embodiment may be composed only of Li, Ti, Zr, and F.

[0015] The solid electrolyte material according to the first embodiment may contain elements that are inevitably mixed in. Examples of such elements are hydrogen, oxygen, or nitrogen. Such elements may be present in the raw material powder of the solid electrolyte material or in the atmosphere for producing or storing the solid electrolyte material.

[0016] In order to further increase the ionic conductivity of the solid electrolyte material, in the solid electrolyte material according to the first embodiment, the ratio of the amount of substance of Li to the total amount of substances of Ti and Zr may be 2.0 or more and 6.0 or less.

[0017] The solid electrolyte material according to the first embodiment may be represented by the following compositional formula (1). Li 6-4b (Ti 1-x Zr x ) b F6 ··· Formula (1) In formula (1), the mathematical expressions: 0 <x <1 and 0 <b ≤ 1.5 are satisfied. The solid electrolyte material having such a composition has high ionic conductivity.

[0018] In order to increase the ionic conductivity of the solid electrolyte material, in formula (1), the mathematical expression: 0.1 ≤ x ≤ 0.8 may be satisfied.

[0019] The upper and lower limit values of the range of x in formula (1) may be defined by any combination selected from the numerical values of 0.1, 0.2, 0.4, 0.5, 0.6, 0.67, and 0.8.

[0020] In order to increase the ionic conductivity of the solid electrolyte material, in formula (1), the mathematical expression: 0.6 ≤ b ≤ 1.0 may be satisfied. In order to further increase the ionic conductivity of the solid electrolyte material, in formula (1), the mathematical expression: 0.8 ≤ b ≤ 0.92 may be satisfied.

[0021] The upper and lower limit values of the range of b in formula (1) may be defined by any combination selected from the numerical values of 0.6, 0.8, 0.85, 0.86, 0.92, and 1.0.

[0022] The solid electrolyte material according to the first embodiment may be crystalline or amorphous.

[0023] The shape of the solid electrolyte material according to the first embodiment is not limited. Examples of the shape are needle-like, spherical, or elliptical. The solid electrolyte material according to the first embodiment may be particles. The solid electrolyte material according to the first embodiment may be formed to have a pellet or plate shape.

[0024] When the shape of the solid electrolyte material according to the first embodiment is, for example, particulate (for example, spherical), the solid electrolyte material may have a median diameter of 0.1 μm or more and 100 μm or less. The median diameter means a particle size when the cumulative volume in the volume-based particle size distribution is equal to 50%. The volume-based particle size distribution is measured, for example, by a laser diffraction measuring device or an image analyzing device.

[0025] The solid electrolyte material according to the first embodiment may have a median diameter of 0.5 μm or more and 10 μm or less. This allows the solid electrolyte material to have higher conductivity. Furthermore, when the solid electrolyte material according to the first embodiment is mixed with other materials such as active materials, the solid electrolyte material according to the first embodiment and the other materials are well dispersed.

[0026] <Method of manufacturing solid electrolyte material> The solid electrolyte material according to the first embodiment can be produced, for example, by the following method.

[0027] Raw material powders are prepared and mixed to obtain a desired composition. The raw material powders may be, for example, halides.

[0028] As an example, if the desired composition is Li 2.8 Ti 0.4 Zr 0.4 In the case of F6, LiF, TiF4, and ZrF4 are mixed in a molar ratio of about 2.8:0.4:0.4. The raw material powders may be mixed in a pre-adjusted molar ratio to offset composition changes that may occur in the synthesis process.

[0029] The raw material powders are reacted with each other mechanochemically (i.e., using the method of mechanochemical milling) in a mixing device such as a planetary ball mill to obtain a reactant. The reactant may be fired in a vacuum or in an inert atmosphere. Alternatively, a mixture of the raw material powders may be fired in a vacuum or in an inert atmosphere to obtain a reactant. The firing is preferably carried out, for example, at 100°C or higher and 300°C or lower for 1 hour or more. In order to suppress composition changes during firing, the raw material powders are preferably fired in a closed container such as a quartz tube.

[0030] By these methods, the solid electrolyte material according to the first embodiment can be obtained.

[0031] Second embodiment The second embodiment will be described below. The matters described in the first embodiment may be omitted.

[0032] The battery according to the second embodiment includes a positive electrode, a negative electrode, and an electrolyte layer. The electrolyte layer is provided between the positive electrode and the negative electrode. At least one selected from the group consisting of the positive electrode, the electrolyte layer, and the negative electrode contains the solid electrolyte material according to the first embodiment. The battery according to the second embodiment has excellent charge / discharge characteristics because it contains the solid electrolyte material according to the first embodiment. The battery may be an all-solid-state battery.

[0033] FIG. 1 shows a cross-sectional view of a battery 1000 according to a second embodiment.

[0034] The battery 1000 according to the second embodiment includes a positive electrode 201, an electrolyte layer 202, and a negative electrode 203. The electrolyte layer 202 is provided between the positive electrode 201 and the negative electrode 203.

[0035] The positive electrode 201 contains positive electrode active material particles 204 and solid electrolyte particles 100 .

[0036] The electrolyte layer 202 contains an electrolyte material, for example, a solid electrolyte material.

[0037] The negative electrode 203 contains negative electrode active material particles 205 and solid electrolyte particles 100 .

[0038] The solid electrolyte particle 100 is a particle made of the solid electrolyte material according to the first embodiment, or a particle containing as a main component the solid electrolyte material according to the first embodiment. Here, the particle containing as a main component the solid electrolyte material according to the first embodiment means a particle in which the component contained most abundantly by mass is the solid electrolyte material according to the first embodiment.

[0039] The positive electrode 201 contains a material capable of absorbing and releasing metal ions (for example, lithium ions). The material is, for example, a positive electrode active material (for example, positive electrode active material particles 204).

[0040] Examples of the positive electrode active material are lithium-containing transition metal oxides, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal oxysulfides, or transition metal oxynitrides. Examples of lithium-containing transition metal oxides are Li(Ni,Co,Al)O2, Li(Ni,Co,Mn)O2, or LiCoO2. In this disclosure, the notation "(Ni,Co,Al)" in the chemical formula indicates at least one element selected from the group of elements in parentheses. That is, "(Ni,Co,Al)" is synonymous with "at least one selected from the group consisting of Ni, Co, and Al." The same applies to other elements.

[0041] The positive electrode active material particles 204 may have a median diameter of 0.1 μm or more and 100 μm or less. When the positive electrode active material particles 204 have a median diameter of 0.1 μm or more, the positive electrode active material particles 204 and the solid electrolyte particles 100 are well dispersed in the positive electrode 201. This improves the charge / discharge characteristics of the battery 1000. When the positive electrode active material particles 204 have a median diameter of 100 μm or less, the lithium diffusion rate in the positive electrode active material particles 204 is improved. This allows the battery 1000 to operate at a high output.

[0042] The positive electrode active material particles 204 may have a larger median diameter than the solid electrolyte particles 100. This allows the positive electrode active material particles 204 and the solid electrolyte particles 100 to be well dispersed in the positive electrode 201.

[0043] To increase the energy density and output of the battery, in the positive electrode 201, the ratio of the volume of the positive electrode active material particles 204 to the sum of the volume of the positive electrode active material particles 204 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.

[0044] A coating layer may be formed on at least a part of the surface of the positive electrode active material particle 204. The coating layer may be formed on the surface of the positive electrode active material particle 204, for example, before mixing with the conductive assistant and the binder. Examples of the coating material contained in the coating layer are a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte. When the solid electrolyte particle 100 contains a sulfide solid electrolyte, the coating material may contain the solid electrolyte material according to the first embodiment in order to suppress oxidative decomposition of the sulfide solid electrolyte. When the solid electrolyte particle 100 contains the solid electrolyte material according to the first embodiment, the coating material may contain an oxide solid electrolyte in order to suppress oxidative decomposition of the solid electrolyte material. Lithium niobate, which has excellent stability at high potential, may be used as the oxide solid electrolyte. By suppressing the oxidative decomposition of the solid electrolyte material, the increase in overvoltage of the battery can be suppressed.

[0045] To increase the energy density and power output of the battery, the positive electrode 201 may have a thickness of 10 μm or more and 500 μm or less.

[0046] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, a solid electrolyte material. The electrolyte layer 202 may be a solid electrolyte layer.

[0047] The electrolyte layer 202 may be composed of only the solid electrolyte material according to the first embodiment. Alternatively, it may be composed of only a solid electrolyte material different from the solid electrolyte material according to the first embodiment. Examples of the solid electrolyte material different from the solid electrolyte material according to the first embodiment are Li2MgX4, Li2FeX4, Li(Al,Ga,In)X4, Li3(Al,Ga,In)X6, or LiI. Here, X is at least one selected from the group consisting of F, Cl, Br, and I.

[0048] Hereinafter, the solid electrolyte material according to the first embodiment will be referred to as a first solid electrolyte material, and a solid electrolyte material different from the solid electrolyte material according to the first embodiment will be referred to as a second solid electrolyte material.

[0049] The electrolyte layer 202 may contain not only the first solid electrolyte material but also the second solid electrolyte material. The first solid electrolyte material and the second solid electrolyte material may be uniformly dispersed in the electrolyte layer 202. A layer made of the first solid electrolyte material and a layer made of the second solid electrolyte material may be stacked along the stacking direction of the battery 1000.

[0050] FIG. 2 shows a cross-sectional view of a battery 2000 according to a second embodiment.

[0051] 2, the battery 2000 may include a positive electrode 201, a first electrolyte layer 212, a second electrolyte layer 222, and a negative electrode 203. That is, the electrolyte layer 202 may include the first electrolyte layer 212 and the second electrolyte layer 222. The first electrolyte layer 212 is disposed between the positive electrode 201 and the negative electrode 203. The second electrolyte layer 222 is disposed between the first electrolyte layer 212 and the negative electrode 203.

[0052] In the battery 2000, the first electrolyte layer 212 may contain the solid electrolyte material according to the first embodiment. Since the solid electrolyte material according to the first embodiment has high oxidation resistance, the solid electrolyte material contained in the second electrolyte layer 222 can be used without being oxidized. As a result, the charge / discharge efficiency of the battery can be improved.

[0053] In the battery 2000, the solid electrolyte material contained in the second electrolyte layer 222 may have a lower reduction potential than the solid electrolyte material contained in the first electrolyte layer 212. This allows the solid electrolyte material contained in the first electrolyte layer 212 to be used without being reduced. As a result, the charge / discharge efficiency of the battery can be improved. For example, when the first electrolyte layer 212 contains the solid electrolyte material according to the first embodiment, the second electrolyte layer 222 may contain a sulfide solid electrolyte to suppress reductive decomposition of the solid electrolyte material.

[0054] To increase the energy density and power output of the battery, the electrolyte layer 202 may have a thickness of 1 μm or more and 1000 μm or less.

[0055] The negative electrode 203 contains a material capable of absorbing and releasing metal ions (for example, lithium ions). The material is, for example, a negative electrode active material (for example, negative electrode active material particles 205).

[0056] Examples of the negative electrode active material are metal materials, carbon materials, oxides, nitrides, tin compounds, or silicides. The metal material may be a single metal or an alloy. Examples of the metal material are lithium metal or lithium alloys. Examples of the carbon material are natural graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, artificial graphite, or amorphous carbon. From the viewpoint of capacity density, suitable examples of the negative electrode active material are silicon (i.e., Si), tin (i.e., Sn), silicides, or tin compounds.

[0057] The negative electrode active material may be selected in consideration of the reduction resistance of the solid electrolyte material contained in the negative electrode 203. For example, when the negative electrode 203 contains the solid electrolyte material according to the first embodiment, the negative electrode active material may be a material capable of absorbing and releasing lithium ions at 0.27 V or more versus lithium. Examples of such negative electrode active materials are titanium oxide, indium metal, or lithium alloys. An example of titanium oxide is Li4Ti5O 12, LiTi2O4, or TiO2. By using the above-mentioned negative electrode active material, it is possible to suppress the reductive decomposition of the solid electrolyte material according to the first embodiment contained in the negative electrode 203. As a result, it is possible to improve the charge / discharge efficiency of the battery.

[0058] The negative electrode active material particles 205 may have a median diameter of 0.1 μm or more and 100 μm or less. When the negative electrode active material particles 205 have a median diameter of 0.1 μm or more, the negative electrode active material particles 205 and the solid electrolyte particles 100 are well dispersed in the negative electrode 203. This improves the charge / discharge characteristics of the battery. When the negative electrode active material particles 205 have a median diameter of 100 μm or less, the lithium diffusion rate in the negative electrode active material particles 205 is improved. This allows the battery to operate at high power.

[0059] The negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100. This allows the negative electrode active material particles 205 and the solid electrolyte particles 100 to be well dispersed in the negative electrode 203.

[0060] In order to increase the energy density and output of the battery, in the negative electrode 203, the ratio of the volume of the negative electrode active material particles 205 to the sum of the volume of the negative electrode active material particles 205 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.

[0061] To increase the energy density and power output of the battery, the negative electrode 203 may have a thickness of 10 μm or more and 500 μm or less.

[0062] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a second solid electrolyte material for the purpose of increasing ion conductivity, chemical stability, and electrochemical stability.

[0063] The second solid electrolyte material may be a sulfide solid electrolyte.

[0064] Examples of sulfide solid electrolytes are Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, or Li 10 GeP2S 12 It is.

[0065] When the electrolyte layer 202 contains the solid electrolyte material according to the first embodiment, the negative electrode 203 may contain a sulfide solid electrolyte in order to suppress reductive decomposition of the solid electrolyte material. By covering the negative electrode active material with the electrochemically stable sulfide solid electrolyte, it is possible to suppress the solid electrolyte material according to the first embodiment from coming into contact with the negative electrode active material. As a result, the internal resistance of the battery can be reduced.

[0066] The second solid electrolyte material may be an oxide solid electrolyte.

[0067] Examples of oxide solid electrolytes include: (i) NASICON-type solid electrolytes such as LiTi2(PO4)3 or elemental substitutions thereof; (ii) Perovskite-type solid electrolytes such as (LaLi)TiO3; (iii) Li 14 ZnGeO 16 LISICON-type solid electrolytes such as Li4SiO4, LiGeO4 or elemental substitutions thereof; (iv) Li7La3Zr2O 12 or a garnet-type solid electrolyte such as an elemental substitution product thereof; or (v) Li3PO4 or its N-substituted derivatives, It is.

[0068] As mentioned above, the second solid electrolyte material may be a halide solid electrolyte.

[0069] Examples of halide solid electrolytes are Li2MgX4, Li2FeX4, Li(Al,Ga,In)X4, Li3(Al,Ga,In)X6, or LiI, where X is at least one selected from the group consisting of F, Cl, Br, and I.

[0070] Other examples of halide solid electrolyte materials include Li a Me b Y c X6. Here, a+mb+3c=6 and c>0 are satisfied. Me is at least one selected from the group consisting of metal elements and metalloid elements other than Li and Y. m represents the valence of Me. "Metalloid elements" are B, Si, Ge, As, Sb, and Te. "Metal elements" are all elements included in Groups 1 to 12 of the periodic table (excluding hydrogen) and all elements included in Groups 13 to 16 of the periodic table (excluding B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se).

[0071] To enhance the ionic conductivity of the halide solid electrolyte material, Me may be at least one selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta, and Nb. The halide solid electrolyte may be Li3YCl6 or Li3YBr6.

[0072] The second solid electrolyte material may be an organic polymer solid electrolyte.

[0073] An example of the organic polymer solid electrolyte is a compound of a polymer compound and a lithium salt.

[0074] The polymer compound may have an ethylene oxide structure. A polymer compound having an ethylene oxide structure can contain a large amount of lithium salt, and therefore can further increase ionic conductivity.

[0075] Examples of the lithium salt are LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.

[0076] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a nonaqueous electrolyte solution, a gel electrolyte, or an ionic liquid for the purpose of facilitating the exchange of lithium ions and improving the output characteristics of the battery.

[0077] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.

[0078] Examples of non-aqueous solvents are cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents, or fluorine solvents. Examples of cyclic carbonate solvents are ethylene carbonate, propylene carbonate, or butylene carbonate. Examples of chain carbonate solvents are dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane, or 1,3-dioxolane. Examples of chain ether solvents are 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents are γ-butyrolactone. Examples of chain ester solvents are methyl acetate. Examples of fluorine solvents are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, or fluorodimethylene carbonate. One type of non-aqueous solvent selected from these may be used alone, or a combination of two or more types of non-aqueous solvents selected from these may be used.

[0079] Examples of the lithium salt are LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used. The concentration of the lithium salt is, for example, in the range of 0.5 mol / L or more and 2 mol / L or less.

[0080] The gel electrolyte may be a polymer material impregnated with a non-aqueous electrolyte, such as polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.

[0081] Examples of cations contained in ionic liquids are: (i) Aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium salts, (ii) aliphatic cyclic ammonium such as pyrrolidiniums, morpholiniums, imidazoliniums, tetrahydropyrimidiniums, piperaziniums, or piperidiniums, or (iii) nitrogen-containing heterocyclic aromatic cations such as pyridiniums or imidazoliums; It is.

[0082] An example of an anion contained in an ionic liquid is PF6 - , BF4 - , SbF6 - , AsF6 - , SO3CF3 - , N(SO2CF3)2 - , N(SO2C2F5)2 - , N(SO2CF3)(SO2C4F9) - , or C(SO2CF3)3 - It is.

[0083] The ionic liquid may contain a lithium salt.

[0084] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a binder for the purpose of improving adhesion between particles.

[0085] Examples of binders are polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polyacrylic acid methyl ester, polyacrylic acid ethyl ester, polyacrylic acid hexyl ester, polymethacrylic acid, polymethacrylic acid methyl ester, polymethacrylic acid ethyl ester, polymethacrylic acid hexyl ester, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene butadiene rubber, or carboxymethylcellulose. Copolymers may also be used as binders. Examples of such binders are copolymers of two or more materials selected from the group consisting of tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene. A mixture of two or more materials selected from these may be used as a binder.

[0086] At least one of the positive electrode 201 and the negative electrode 203 may contain a conductive additive to reduce electronic resistance.

[0087] Examples of the conductive additive include: (i) Graphites, such as natural or synthetic graphite; (ii) Carbon blacks such as acetylene black or ketjen black; (iii) conductive fibers, such as carbon or metal fibers; (iv) fluorocarbons, (v) Metal powders such as aluminum; (vi) conductive whiskers such as zinc oxide or potassium titanate; (vii) a conductive metal oxide, such as titanium dioxide; or (viii) conductive polymers such as polyaniline, polypyrrole, or polythiophene; In order to reduce costs, the above-mentioned conductive assistant (i) or (ii) may be used.

[0088] Examples of the shape of the battery according to the second embodiment are a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, or a laminate type.

[0089] The battery according to the second embodiment may be manufactured, for example, by preparing a material for forming a positive electrode, a material for forming an electrolyte layer, and a material for forming a negative electrode, and producing a laminate in which the positive electrode, the electrolyte layer, and the negative electrode are arranged in this order by a known method. EXAMPLES

[0090] Hereinafter, the present disclosure will be described in more detail with reference to examples and comparative examples.

[0091] <Example 1> (Preparation of solid electrolyte materials) In an argon atmosphere having a dew point of -60°C or less (hereinafter referred to as "dry argon atmosphere"), LiF, TiF4, and ZrF4 were prepared as raw material powders in a molar ratio of LiF:TiF4:ZrF4 = 2.8:0.4:0.4. These materials were ground and mixed in a mortar. The resulting mixture was milled at 500 rpm for 12 hours using a planetary ball mill. In this manner, a powder of the solid electrolyte material according to Example 1 was obtained. The solid electrolyte material according to Example 1 was composed of Li 2.8 Ti 0.4 Zr 0.4 It had a composition represented by F6.

[0092] (Evaluation of ionic conductivity) FIG. 3 shows a schematic diagram of a pressing die 300 used to evaluate the ionic conductivity of the solid electrolyte material.

[0093] The pressure molding die 300 had an upper punch 301, a frame 302, and a lower punch 303. The frame 302 was made of insulating polycarbonate. The upper punch 301 and the lower punch 303 were made of electronically conductive stainless steel.

[0094] Using the pressure molding die 300 shown in FIG. 3, the ionic conductivity of the solid electrolyte material according to Example 1 was evaluated by the following method.

[0095] In a dry atmosphere having a dew point of −30° C. or less, the powder of the solid electrolyte material according to Example 1 was filled into the inside of the pressure molding die 300. In the inside of the pressure molding die 300, a pressure of 400 MPa was applied to the solid electrolyte material according to Example 1 using the upper punch 301 and the lower punch 303.

[0096] While the pressure was still applied, the upper punch 301 and the lower punch 303 were connected to a potentiostat (Princeton Applied Research, VersaSTAT4) equipped with a frequency response analyzer. The upper punch 301 was connected to a working electrode and a terminal for measuring potential. The lower punch 303 was connected to a counter electrode and a reference electrode. The impedance of the solid electrolyte material was measured by electrochemical impedance measurement at room temperature.

[0097] FIG. 4 is a graph showing a Cole-Cole plot obtained by impedance measurement of the solid electrolyte material according to Example 1.

[0098] In FIG. 4, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest was considered to be the resistance value for the ion conduction of the solid electrolyte material. The real value is indicated by the arrow R SEUsing the resistance value, the ionic conductivity was calculated based on the following formula (2). σ = (R SE ×S / t) -1 (2) Here, σ represents ion conductivity. S represents the contact area of ​​the solid electrolyte material with the punch upper portion 301 (equal to the cross-sectional area of ​​the hollow portion of the frame mold 302 in FIG. 3). R SE represents the resistance value of the solid electrolyte material in impedance measurement, and t represents the thickness of the solid electrolyte material (i.e., the thickness of the layer formed from the powder 101 of the solid electrolyte material in FIG. 3).

[0099] The ionic conductivity of the solid electrolyte material according to Example 1 measured at 25° C. was 1.94×10 -6 S / cm.

[0100] (Battery Construction) In a dry argon atmosphere, the solid electrolyte material according to Example 1 and the active material LiCoO2 were prepared in a volume ratio of 30:70. These materials were mixed in an agate mortar. In this way, a positive electrode mixture was obtained.

[0101] Next, LiCl and YCl3 were prepared in a molar ratio of LiCl:YCl3 = 3:1. These materials were ground and mixed in a mortar. The resulting mixture was milled at 500 rpm for 12 hours using a planetary ball mill. In this way, a halide solid electrolyte (hereinafter referred to as "LYC") having a composition represented by Li3YCl6 was obtained.

[0102] In an insulating cylinder having an inner diameter of 9.5 mm, LYC (60 mg), the solid electrolyte material according to Example 1 (26 mg), and the above-mentioned positive electrode mixture (9.1 mg) were laminated in this order. A pressure of 300 MPa was applied to the obtained laminate, and a second electrolyte layer, a first electrolyte layer, and a positive electrode were formed. That is, the first electrolyte layer formed from the solid electrolyte material according to Example 1 was sandwiched between the second electrolyte layer and the positive electrode. The thicknesses of the second electrolyte layer and the first electrolyte layer were 450 μm and 150 μm, respectively.

[0103] Next, metal In (thickness: 200 μm) was laminated on the second electrolyte layer. A pressure of 80 MPa was applied to the resulting laminate to form a negative electrode.

[0104] Next, current collectors made of stainless steel were attached to the positive and negative electrodes, and current collecting leads were attached to the current collectors.

[0105] Finally, the inside of the insulating cylinder was isolated from the outside atmosphere by using an insulating ferrule, and the inside of the cylinder was sealed. In this manner, the battery according to Example 1 was obtained.

[0106] (Charge / discharge test) 5 is a graph showing the initial discharge characteristics of the battery according to Example 1. The initial charge / discharge characteristics were measured by the following method.

[0107] The battery according to Example 1 was placed in a thermostatic chamber at 85°C.

[0108] 27μA / cm 2 The battery according to Example 1 was charged until a voltage of 3.6 V was reached at a current density of 0.02 C, which corresponds to a 0.02 C rate.

[0109] Next, 27 μA / cm 2 The battery according to Example 1 was discharged at a current density of 0.1 V until a voltage of 1.9 V was reached.

[0110] As a result of the charge / discharge test, the battery according to Example 1 had an initial discharge capacity of 720 μAh.

[0111] <Examples 2 to 11> (Preparation of solid electrolyte materials) In Examples 2 to 11, LiF, TiF4, and ZrF4 were prepared as raw material powders so that the molar ratio of LiF:TiF4:ZrF3=(6-4b):(1-x)b:xb was satisfied.

[0112] Except for the above, the solid electrolyte materials according to Examples 2 to 11 were obtained in the same manner as in Example 1.

[0113] For the solid electrolyte materials according to Examples 2 to 11, the values ​​of x, b, and Li / (Ti+Zr) molar ratio are shown in Table 1.

[0114] (Evaluation of ionic conductivity) The ionic conductivity of the solid electrolyte materials according to Examples 2 to 11 was measured in the same manner as in Example 1. The measurement results are shown in Table 1.

[0115] (Charge / discharge test) The solid electrolyte materials according to Examples 2 to 11 were used to obtain the batteries according to Examples 2 to 11 in the same manner as in Example 1.

[0116] Charge and discharge tests were carried out on the batteries according to Examples 2 to 11 in the same manner as in Example 1. The batteries according to Examples 2 to 11 were charged and discharged well, similar to the battery according to Example 1.

[0117] <Comparative Example 1> As a solid electrolyte material, Li 2.8 Ti 0.4 Zr 0.4 LiBF4 was used instead of F6.

[0118] The ionic conductivity of LiBF4 was measured in the same manner as in Example 1. The ionic conductivity measured at 25°C was 6.67 × 10 -9 S / cm.

[0119] A battery according to Comparative Example 1 was obtained in the same manner as in Example 1, except that LiBF4 was used as the solid electrolyte material.

[0120] A charge / discharge test was carried out on the battery according to Comparative Example 1 in the same manner as in Example 1. As a result, the battery according to Comparative Example 1 had an initial discharge capacity of 0.01 μAh or less. That is, the battery according to Comparative Example 1 was neither charged nor discharged.

[0121] Table 1 shows the solid electrolyte materials in Examples 1 to 11 and Comparative Example 1 and the evaluation results.

[0122] [Table 1]

[0123] <Consideration> The solid electrolyte materials according to Examples 1 to 11 have a melting point of 1×10 -8 The solid electrolyte material of the comparative example has a high ionic conductivity of 1×10 -8 It has low ionic conductivity of less than S / cm.

[0124] The solid electrolyte materials of Examples 1, 2, 3, 4, and 10 have the same value of x (i.e., x=0.5). As is clear from a comparison of Examples 1, 2, and 4 with Examples 3 and 10, in solid electrolyte materials having the same value of x, when 0.8≦b≦0.92 is satisfied, the ionic conductivity of the solid electrolyte material is further increased.

[0125] The batteries according to Examples 1 to 11 were all charged and discharged at 85° C. On the other hand, the battery according to Comparative Example 1 was neither charged nor discharged.

[0126] The solid electrolyte materials according to Examples 1 to 11 do not contain sulfur and therefore do not generate hydrogen sulfide.

[0127] As described above, the solid electrolyte material according to the present disclosure is suitable for providing a battery that has high lithium ion conductivity and can be charged and discharged well. [Industrial Applicability]

[0128] The solid electrolyte material of the present disclosure is used, for example, in an all-solid-state lithium ion secondary battery. [Explanation of symbols]

[0129] 100 solid electrolyte particles 101 Solid electrolyte material powder 201 Positive electrode 202 Electrolyte layer 212 1st electrolyte layer 222 Second electrolyte layer 203 Negative electrode 204 Positive electrode active material particles 205 Negative electrode active material particles 300 Pressure forming die 301 Punch top 302 Frame type 303 Punch bottom 1000 batteries 2000 batteries

Claims

1. Li, Ti, Zr, and F; Represented by the following composition formula (1): Li 6-4b (Ti 1-x Zr x ) b F 6 ...Formula (1) where 0<x<1 and 0.6≦b≦0.92 are satisfied. Solid electrolyte material.

2. The ratio of the amount of substance of Li to the sum of the amounts of substance of Ti and Zr is 2.0 or more and 6.0 or less; The solid electrolyte material according to claim 1 .

3. The formula: 0.1≦x≦0.8 is satisfied; The solid electrolyte material according to claim 1 .

4. positive electrode, a negative electrode, and an electrolyte layer provided between the positive electrode and the negative electrode; Equipped with At least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 3. battery.

5. the electrolyte layer includes a first electrolyte layer and a second electrolyte layer; the first electrolyte layer is disposed between the positive electrode and the negative electrode; the second electrolyte layer is disposed between the first electrolyte layer and the negative electrode; The first electrolyte layer contains the solid electrolyte material.

5. The battery of claim 4.

Citation Information

Patent Citations

  • B3+, Al3 +, Ti4 +, Y3+ F-codoped solid electrolyte Li7La3Zr2Ol2

    CN102867988A

  • Lithium secondary battery and electrode for lithium secondary battery

    JP2008277170A

  • Method of manufacturing sulfide solid electrolyte material, sulfide solid electrolyte material, and lithium battery

    JP2011129312A

  • Electrode active material, preparation method thereof, and electrode and lithium battery containing the same

    US20130071745A1

  • Battery

    WO2019146217A1